2006
DOI: 10.1128/aac.01149-05
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Determination of Plasma Imipenem Concentrations in Critically Ill Children

Abstract: Plasma imipenem concentrations were measured in 19 critically ill children (median age, 0.8 year; range, 0.02 to 12.9 years). Wide interindividual variations (2 to 4؋ at peak and >10؋ at trough concentrations) resulted in unpredictable plasma levels in several children. To avoid subtherapeutic drug levels, we recommend treatment with at least 100 mg/kg of body weight/day of imipenem-cilastatin for critically ill children requiring such therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 22 publications
3
30
0
1
Order By: Relevance
“…Similar observations were also made with imipenem in adult patients [2,3], suggesting that drug adjustment algorithms used at the bedside might not be always accurate in unstable ICU patients, and that drug monitoring should be used more often [1]. …”
Section: Introductionmentioning
confidence: 61%
“…Similar observations were also made with imipenem in adult patients [2,3], suggesting that drug adjustment algorithms used at the bedside might not be always accurate in unstable ICU patients, and that drug monitoring should be used more often [1]. …”
Section: Introductionmentioning
confidence: 61%
“…Since January 2010, TDM has been available 4 days per week. TDM measurement: Prior to 2010, plasma concentrations of imipenem/cilastatin and meropenem were measured separately by high-performance liquid chromatography coupled with ultraviolet detection, using adaptations of previously published methods [31,32]. Since 2010, imipenem/cilastatin and meropenem have been analyzed simultaneously using a multiplex assay by ultra-performance liquid chromatography coupled with tandem mass spectrometry [24,25].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…One study reported that the PK of imipenem in critically ill children (median [range] age of 0.8 years [0.02 to 12.9]) was highly variable with unpredictable plasma concentrations observed in several children [127]. The mean (± SD) steady-state half-life, CL and V D were 1.35 hours (± 0.38), 0.34 L/h/kg (± 0.14), and 0.46 L/kg (± 0.25), respectively [127]. These values were similar to the values reported in other non-critically ill children and healthy adults [125,126].…”
Section: Pharmacokinetic Studies In Critically Ill Childrenmentioning
confidence: 99%
“…Nonetheless, some physiological parameters during critical illness altered imipenem PK, including blood pressure, creatinine clearance, and bicarbonate and lactate levels. For instance, elimination rates were reduced in patients with high lactate and low bicarbonate levels, possibly due to poor perfusion to the kidneys, and elimination rates correlated with creatinine clearance [127]. …”
Section: Pharmacokinetic Studies In Critically Ill Childrenmentioning
confidence: 99%